LEGAL PROTECTION FOR FINAL CONSUMERS FOR BUYING FLATS FROM INITIAL CONSUMERS RELATED TO BINDING AGREEMENTS OF SALE AND BUYING IN PAID BASED ON THE PRINCIPLE OF GOOD FAITH - Christy Giriputri; Yani Pujiwati; Betty Rubiati (Fakultas Hukum Universitas Padjadjaran, 2023)
Apartment ownership has become an important phenomenon in the rapidly growing property industry. The increase in population growth is not balanced with the availability of existing land. Flats are often sold by early consumers with a Sales and Purchase Binding Agreement in full without the developer's knowledge. The aim of the research is to gain an understanding of buying and selling apartments between early consumers and buyers based on PPJB Paid Off and legal protection for buyers. This study uses a normative juridical approach, which is descriptive analysis in nature, with a library research stage that includes primary, secondary and tertiary legal materials as well as field research, data collection techniques carried out through document studies and interviews. The results of the study show that buying and selling apartments between initial consumers and buyers with paid PPJB can be considered with the principle of good faith by taking into account several points of caution as early consumers and buyers. Buyers with good intentions should upgrade the PPJB to a Sale and Purchase Deed (AJB) so that the Certificate of Ownership of the flat unit can be issued in accordance with the name of the buyer.